Pengaruh Harga, Pelayanan dan Promosi terhadap Keputusan Pembelian Konsumen : Survei pada Pengguna Aplikasi Gojek di Surakarta - Fatin Navi Cahyati; Sumaryanto Sumaryanto (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
Gojek is a company operating in the transportation sector, Gojek's head office is in Jakarta, Indonesia. Gojek was founded by Nadiem Makarim, an Indonesian citizen who graduated with a Master of Business Administration from Harvard Business School. The scope of this research was carried out on consumers who use Gojek services in the Surakarta area. The aim of this research is to analyze the significance of the influence of price, service and promotion on consumer purchasing decisions for Gojek customers in Surakarta. This research is a survey. This type of data uses quantitative data. The data source uses primary data. The population in this research are all consumers who use Gojek services in Surakarta. The number of samples used in this research was 110 people. The sampling technique uses purposive sampling. The data collection technique uses a questionnaire. Data analysis uses descriptive analysis, multiple linear regression test, t test, F test and coefficient of determination test. The research results show that price has no significant effect on consumer purchasing decisions for Gojek customers in Surakarta, service has a significant effect on purchasing decisions in Surakarta and promotions have a significant effect on purchasing decisions for Gojek customers in Surakarta.